2019
DOI: 10.1039/c8sc05813j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photoredox conversion of alcohol to aldehyde and H2 by heterointerface engineering of bimetal–semiconductor hybrids

Abstract: An anisotropic bimetal–semiconductor heterostructure with efficient charge carrier generation, transfer and utilization for plasmon-enhanced photoredox catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 73 publications
(122 reference statements)
1
49
0
Order By: Relevance
“…Screening of different light sources showed that blue light slightly increased the yield. The apparent quantum efficiency (AQE) was 0.54 % at 450 nm (see the Supporting Information) [40c] . Furthermore, increasing or decreasing the loading amounts of catalyst did not improve the yield (Table 1, entries 20 and 21).…”
Section: Resultsmentioning
confidence: 99%
“…Screening of different light sources showed that blue light slightly increased the yield. The apparent quantum efficiency (AQE) was 0.54 % at 450 nm (see the Supporting Information) [40c] . Furthermore, increasing or decreasing the loading amounts of catalyst did not improve the yield (Table 1, entries 20 and 21).…”
Section: Resultsmentioning
confidence: 99%
“…Integrating diverse functional materials into a single heterojunction with a precise design holds great promise for constructing efficient photocatalysts, owing to the synergistic properties induced by the interactions between these components . Li et al.…”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
“…[82]. Copyright 2020 Elsevier photocatalyst, is applied to the transformation of BA to H 2 and BAD under Vis-NIR light irradiation [76]. The results show that the Au-Pt@CdS composite exhibits higher production of H 2 and BAD than CdS deposited Au nanorods (Au@ CdS) and CdS deposited Pt-covered Au nanorods (Au@ Pt@CdS), indicating that the spatial distribution of metal components and the composition of bimetal-semiconductor composites affect photocatalytic activity.…”
Section: Ba Oxidation Coupled With Photocatalytic H 2 Generationmentioning
confidence: 99%